Achieving Gender Equity in Nigerian Basic Science and Technology Classrooms with Metacognitive Skills Package - Ozoji, B. Ebele; Iliya, Godiya B.; Garba, Saad A.; Isuwa, S. Damjik (Kashere Journal of Education, 2022)
The study investigated the possibility of achieving gender equity in Basic Science and Technology classrooms with Metacognitive Skills Package in Pankshin, Plateau State, Nigeria. The study adopted the non-randomized pre-test, post-test quasi-experimental control group design. The population comprised 1,873 Junior Secondary two students out of which 235 students constituted the sample. Two research questions and two hypotheses guided the study. The Basic Science and Technology Achievement Tests with reliability index of .85 established using the Cronbach alpha method was used to collect data from the sample. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 25.0. Research questions were answered using mean and standard deviation while hypotheses were tested using Analysis of Covariance at .05 level of significance. The study revealed that students taught with metacognitive strategy achieved better in Basic Science and Technology when compared to those taught using the lecture method. It was also revealed that metacognitive skills package enhanced achievement of both male and female students thereby improving gender equity in Basic Science and Technology. Based on the findings of this study, it was recommended that Basic Science and Technology teachers should teach their students with metacognitive skills package to enhance students’ achievement in the subject. Metacognitive skills package should also be used by teachers as a gender-friendly package to improve gender equity in Basic Science and Technology.